BRIS AT IDX: A LOOK AT HOW SHARIAH BANK MERGER WORKS IN INDONESIA - Andryan Liandi; Christine S.T. Kansil (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This article provides a comprehensive exploration and analysis of the complex legal framework surrounding the merger of PT Bank Syariah Mandiri, PT Bank BRI syariah Tbk, and PT Bank BNI Syariah, resulting in the establishment of Bank Syariah Indonesia (BSI). The analysis meticulously categorizes the legal requirements applicable to both private and public Shariah banks, referencing key regulations such as POJK 41/2019, Law 40/2007, POJK 15/2020, POJK 74/2016, and others. The study delves into the essential elements of the merger process, navigating through the intricacies involved in formulating a comprehensive merger plan. This includes a detailed examination of share evaluation methodologies and the resolution of associated rights and obligations. The article places significant emphasis on the disclosure of material facts, highlighting the importance of transparently communicating information that has the potential to impact stakeholders. Additionally, the analysis extends to the multifaceted approval processes required for the successful execution of the merger, encompassing internal approvals from boards of directors and commissioners, as well as regulatory bodies. The article sheds light on the intricate procedures and criteria outlined by the Indonesia Stock Exchange (IDX) regarding such transformative transactions, further adding complexity to the overall process.